A review of immobilization techniques to improve the stability and bioactivity of lysozyme. Issue 2 (3rd April 2021) - Anastas, Paul T.; Rodriguez, Alina; de Winter, Tamara M.; Coish, Philip; Zimmerman, Julie B.
ABSTRACT: Lysozyme is a naturally occurring enzyme with antimicrobial activity that has gained significant attention for its potential use in a range of industrial applications. Due to its low toxicity, lysozyme has been considered for use in food, packaging, medicine, medical device and cosmetics. In recent decades, researchers have been working towards extending the lifespan and bioactivity of lysozyme for use in these applications. The immobilization of lysozyme on solid supports has shown positive results as demonstrated by increased stability and extended half-life of the enzyme. In this scoping review, the materials and methods utilized for the immobilization of lysozyme and resulting bioactivities will be reviewed and discussed. GRAPHICAL ABSTRACT: UF0001